PROJECT-BASED CHEMISTRY LEARNING DESIGN THROUGH LOCAL RESOURCES USE AT SMA NEGERI KAHAYAN TENGAH, PULANG PISAU DISTRICT - Fatchiyatun Ni'mah; Syarpin Syarpin; Abdul Hadjranul Fatah; Alda Alda; M. Naufal Pasha (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
Central Kahayan State High School is located in Central Kahayan District, Pulang Pisau Regency, Central Kalimantan. The pandemic period resulted in several changes in the implementation of learning. One is that face-to-face learning activities must be carried out online, resulting in limited interaction between teachers and students. The allocation of cut learning time leads to a lack of time for learners to understand the concept of the material. These obstacles experienced result in a reduction in the quality of learning and a decrease in student motivation in the learning process. Based on the existing problems, the idea emerged as a solution by holding project-based learning design training through local resources. Through this training, it is hoped that teachers will have more knowledge and insight into designing innovative learning by utilizing local wisdom and potential. In general, the objectives of community service implemented are 1) increasing motivation to provide innovation in learning activities, 2) improving skills for teachers to design project-based learning activities, and 3) increasing the motivation and enthusiasm for learning of students